Estimation of the Transport and Carboxylation Components of the Intracellular Limitation to Leaf Photosynthesis - Jones, H. G. (1972)
A model is presented which enables gas exchange data to be used to partition the intracellular resistance to leaf photosynthesis into carboxylation and transport components. A basic assumption is that the over-all kinetics of the carboxylation reaction fit the Michaelis-Menten equation. The model was tested for cotton (Gossypium hirsutum L., var. Deltapine Smoothleaf), where photorespiration was suppressed by using gas mixtures containing less than 1.5% oxygen. It was concluded that the transport resistance formed the major component of the intracellular resistance for the plants studied. However, in some cases the major intracellular factor limiting photosynthesis, at an ambient CO(2) concentration of 600 ng cm(−3), was the carboxylation system, which was close to saturation.